Compuflo®-Assisted Training vs Conventional Training for the Identification of the Ligamentum Flavum with an Epidural Simulator: A Brief Report - Emanuele Capogna; Alessandra Coccoluto; Giovanni Gibiino; Angelica Del Vecchio (Anesthesiology Research and Practice)
The ability of recognizing the ligamentum flavum is the first, crucial, important skill to teach novices when they are learning the epidural technique. The aim of this preliminary prospective study was to evaluate whether the Compuflo® Epidural instrument may help inexperienced trainees to better identify the ligamentum flavum during an epidural simulator training session. Compuflo® reduced the total number of attempts to identify the ligamentum flavum and increased three fold the chance to identify it at the first attempt during a simulator-assisted training module, making this identification easier for inexperienced trainees. This trial is registered with NCT03812926.